PENGARUH KEAHLIAN PEMAKAI, PROGRAM PELATIHAN DAN PENDIDIKAN, UKURAN ORGANISASI, DAN FORMALISASI PENGEMBANGAN SISTEM TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Studi Kasus pada PT Kusumahadi Santosa di Karanganyar) - Djoko Kristianto, Rizky Ages Purnawati, Dewi Saptantinah Puji Astuti & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
Accounting information systems is very important in the institution to support the smooth performance of the institution, an institution is required to assess the performance of good financial statements and complete, therefore it is necessary also an accounting information system supported by computerized information technology. This study aimed to determine whether user expertise, program training and education, organizational size, and formalitation development system to affect the performance of accounting information system. The study was conducted at PT Kusumahadi Santosa, Karanganyar. The sample include accounting and employed totaling 30 respondents. The data were collected through questionnaire measured using the likert scale. The data were analyzed using the validity test, reliability test, classical assumption test, multiple regression test, which is processed with SPSS. The result of this research indicate that user expertise, organizational size, and formalitation development system positively effecting to affect the performance of accounting information system, but program training and education negative effecting to affect the performance of accounting information system.Keywords: Performance, Accounting Information System, User Expertise, Program training and Education, Organizational Size, Formalitation Development System.